2002
DOI: 10.1002/tea.10037
|View full text |Cite
|
Sign up to set email alerts
|

When genres meet: Inquiry into a sixth‐grade urban science class

Abstract: In this study, we explore oral and written work (plays and rap songs) of students in a sixth‐grade all African‐American urban science class to reveal ways affective and social aspects are intertwined with students' cognition. We interpret students' work in terms of the meeting of various genres brought by the students and teachers to the classroom. Students bring youth genres, classroom genres that they have constructed from previous schooling, and perhaps their own science genres. Teachers bring their favored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 12 publications
0
36
0
Order By: Relevance
“…Teachers and scholars have become aware of this conflict and have sought ways to bridge the apparent cultural divide that exists between learning to use the language of science and maintaining cultural identity (Reveles, Cordova, & Kelly, 2004;Varelas et al, 2002). This study examines the language practices that emerged as one teacher attempted to alter the language practices of her classroom to promote the appropriation of science language.…”
Section: From Faux Bubba To Using Science Languagementioning
confidence: 99%
See 2 more Smart Citations
“…Teachers and scholars have become aware of this conflict and have sought ways to bridge the apparent cultural divide that exists between learning to use the language of science and maintaining cultural identity (Reveles, Cordova, & Kelly, 2004;Varelas et al, 2002). This study examines the language practices that emerged as one teacher attempted to alter the language practices of her classroom to promote the appropriation of science language.…”
Section: From Faux Bubba To Using Science Languagementioning
confidence: 99%
“…This use of everyday and scientific forms of language becomes pertinent when considering how students' experience with scientific language has served as a gatekeeper to student learning (Brown, 2004(Brown, , 2006Varelas et al, 2002). Research has demonstrated that perhaps the most contentious aspect of minority children's experiences in classrooms involves the conflicting features of their communicative style with those valued by the teacher and classroom (Gee, 1999;Malcolm, 1989;Williams, 1991).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the diversified approach in science classrooms is more consistent with science educators like Varelas et al (2002) and proponents for writing eco-mysteries (e.g., El-Hindi, 2003). While not diminishing the importance of using canonically accurate scientific discourse in formal writing contexts, from this perspective children are expected to "cross borders" from everyday language conventions to more formal genres with appropriate scaffolding or support from teachers (Prain, 2006;Saul, 2004).…”
Section: Storytelling In Sciencementioning
confidence: 63%
“…Broadly, genres are purposive social processes like routines or templates employed by individuals and groups to interact meaningfully with particular audiences in particular contexts (Varelas, Becker, Luster, & Wenzel, 2002). In science classes multiple genres meet; they relate specifically to schooling, science disciplines and youth cultures.…”
Section: Storytelling In Sciencementioning
confidence: 99%